Evaluation of cardiorespiratory parameters in dogs undergoing laparoscopic versus open gonadectomy with spontaneous ventilation anaesthesia: a pilot study - di Virgilio, Fabrizio; Manfredini, Sara; Formaggini, Luca (Journal of Veterinary Healthcare, 2020)
This pilot study aims to compare cardiorespiratory parameters in female dogs that underwent either laparoscopic or open elective gonadectomy with spontaneous ventilation anaesthesia. Records of 77 client-owned female dogs were reviewed. Patients were divided into two groups: laparoscopic surgery (L group, n 47) and open abdominal surgery (O group, n 30). The end-tidal carbon dioxide, respiratory rate, oxygen saturation, heart rate, non-invasive arterial blood pressure and length of procedure were recorded and statistically evaluated. Once normality of the sample data has been assessed, equality between the groups was analysed with two-sample Student’s or Welch’s t-test, whether the hypothesis of variance equality, through an F-test, was verified or not. A value of p <0.05 was considered statistically significant. No statistically significant difference was found between groups regarding the end-tidal carbon dioxide, oxygen saturation, respiratory rate, heart rate, systolic and medium arterial pressure values. Mean diastolic pressure was lower in the L group. The procedure length between the two groups was statistically different: laparoscopy was shorter than open surgery. In spontaneously ventilating female dogs, the cardiorespiratory parameters evaluated seem not to be affected by the presence of pneumoperitoneum when intrabdominal pressure is kept between 8 and 10 mmHg. The pilot nature of the study and the shorter laparoscopic surgery length could bias these results. However, in the author’s opinion, these findings confirm the interest of laparoscopy and the small impact of this mini-invasive technique in healthy patients.
Keywords: End-tidal carbon dioxide; laparoscopy; mini-invasive surgery; pneumoperitoneum; spontaneous ventilation; veterinary anaesthesia